2020
DOI: 10.32598/ptj.10.1.437.1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Knee Joint Position Sense After Anterior Cruciate Ligament Reconstruction in Male Soccer Players

Abstract: Purpose: Anterior Cruciate Ligament (ACL) injury is the most common knee ligament injury during exercise, with a frequency of 36.9 per 100000 individuals. The characteristics of this injury are proprioception dysfunction. The present study aimed to investigate the knee proprioception after the reconstruction of ACL in soccer players. Methods: The study sample of this study was 20 elite male soccer players with an ACL injury experiencing post-reconstruction. The knee joint position sense of the study subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…For this reason, static proprioception tests are not practical enough because inactive movements do not stimulate the muscle spindle, which is a very sensitive mechanoreceptor [6]. Studies have shown that after damage to the joint capsule, ligament, labrum, or muscles involved, the proprioception gets impaired [7][8][9][10]. Damage to the tissues that contain mechanoreceptors causes a relative reduction in afferent messages, which can lead to impaired proprioception and make a person prone to re-injury due to a decrease in proprioceptive feedback [11].…”
Section: Proprioception Joint Position Sense Upper Limb Image Capture Techniquementioning
confidence: 99%
“…For this reason, static proprioception tests are not practical enough because inactive movements do not stimulate the muscle spindle, which is a very sensitive mechanoreceptor [6]. Studies have shown that after damage to the joint capsule, ligament, labrum, or muscles involved, the proprioception gets impaired [7][8][9][10]. Damage to the tissues that contain mechanoreceptors causes a relative reduction in afferent messages, which can lead to impaired proprioception and make a person prone to re-injury due to a decrease in proprioceptive feedback [11].…”
Section: Proprioception Joint Position Sense Upper Limb Image Capture Techniquementioning
confidence: 99%